“Stage Irish” in “Britain’s Oldest Colony”: Introductory Remarks Towards an Analysis of the Influence of the McNulty Family on Newfoundland Music - Byrne, Pat (Ethnologies, 1991)
The McNulty Family, a New York based Irish-American trio, had a pervasive influence on Newfoundland music from the 1930s to the 1970s. The group’s music was introduced to the island by a St. John’s merchant who sold their records throughout the island and sponsored local radio programs for over thirty years. The group’s popularity and influence on the repertoires of local singers are directly related to Newfoundlanders’ search for musical autonomy during a period of political and social change — the change from a British Colony to a Canadian Province, and the emergence of a new middle class.